Observational constraints to boxy/peanut bulge formation time. (3rd June 2017) - Pérez, I.; Martínez-Valpuesta, I.; Ruiz-Lara, T.; de Lorenzo-Caceres, A.; Falcón-Barroso, J.; Florido, E.; González Delgado, R. M.; Lyubenova, M.; Marino, R. A.; Sánchez, S. F.; Sánchez-Blázquez, P.; van de Ven, G.; et al.
Abstract: Boxy/peanut bulges are considered to be part of the same stellar structure as bars and both could be linked through the buckling instability. The Milky Way is our closest example. The goal of this Letter is to determine if the mass assembly of the different components leaves an imprint in their stellar populations allowing the estimation the time of bar formation and its evolution. To this aim, we use integral field spectroscopy to derive the stellar age distributions, SADs, along the bar and disc of NGC 6032. The analysis clearly shows different SADs for the different bar areas. There is an underlying old (≥12 Gyr) stellar population for the whole galaxy. The bulge shows star formation happening at all times. The inner bar structure shows stars of ages older than 6 Gyr with a deficit of younger populations. The outer bar region presents an SAD similar to that of the disc. To interpret our results, we use a generic numerical simulation of a barred galaxy. Thus, we constrain, for the first time, the epoch of bar formation, the buckling instability period and the posterior growth from disc material. We establish that the bar of NGC 6032 is old, formed around 10 Gyr ago while the buckling phase possibly happened around 8 Gyr ago. All these results point towards bars being long-lasting even in the presence of gas.